Geochemical characteristics of crude oil in the eastern of Qinnan sag, Bohai Bay Basin, Eastern China - Shi, Xukai; Liu, Yan; Wang, Deying; Liu, Feng; Wang, Feilong; Wen, Zhigang; Xie, Xiaomin; Wu, Yuanzhe; Lu, Zhongdeng (Frontiers in Earth Science, 2022)
The oil and gas exploration degree of Qinnan sag is low. In this paper, all the 17 Crude oil samples from the four reservoirs in the eastern Qinnan sag were taken as the research object. Research methods include GC-MS, stable carbon isotopic of crude oil and group components and other analytical methods. The geochemical characteristics of crude oil were studied by the main parameters, Pr/ph, γ/C31 hopane, Ts/Tm, 4MSI and C29 sterane isomerization. The results show that most of the hydrocarbon generating parent materials of all the 17 crude oil are reductive lacustrine sedimentary organic matter with higher salinity. The crude oil of Es12 is mainly derived from low aquatic algae, and the crude oil of Ed3, Ek and Mz shows the characteristics of a mixed source. The maturation characteristics of crude oils are low mature-mature. The stable carbon isotope of oil and the components is in the range of -30‰ ~ -26‰, which shows the distribution characteristics of δ13CST<δ13CASP<δ13CNOS<δ13CAR. The characteristics in B-6, C-1 and C-3 of crude oils show the heavy δ13CASP and high abundance of hopane, indicating that there is more contribution from bacterial sources. The crude oil from Es12 is mainly the contribution of Es1 source rocks. The crude oil of Mz, Ek and Ed3 is mainly the mixed source of Es1 and Es3 source rocks, and Es3 is the main source, and the oil source may mainly come from the southeast subsag. The carbon isotope of the component in Block D can be divided into two kinds of crude oil, which may contribute to the oil source of the Bozhong sag. The eastern of Qinnan sag has great hydrocarbon potential.